Comparison of the efficacy and safety of baloxavir versus those of oseltamivir in pediatric patients with influenza: a meta-analysis - Chen, Sheng; Hua, Lingling (Frontiers in Microbiology, 2025)
ObjectiveBaloxavir is a ribonucleic acid polymerase inhibitor that effectively alleviates influenza symptoms in adults and adolescents. This meta-analysis aimed to comprehensively compare the efficacy and safety of baloxavir with those of oseltamivir in pediatric patients with influenza.MethodsA comprehensive study search was performed by encompassing multiple electronic databases, including PubMed, Web of Science, Embase, the Cochrane Library, Wan Fang, VIP, and CNKI, from database establishment to June 2025. Studies comparing the efficacy and safety of baloxavir and oseltamivir in pediatric patients with influenza were included.ResultsA total of 10 studies, including 2,106 patients receiving baloxavir and 2,567 patients receiving oseltamivir, were included in the analysis. The pooled analysis indicated that baloxavir resulted in a shorter duration of symptoms and duration of fever than did oseltamivir (both p < 0.01). In the subgroup analysis, the statistical significance of the duration of symptoms remained unchanged in the subgroups of influenza types A and B, as well as in influenza A subtypes H1N1pdm09 and H3N2A (all p < 0.05). However, in terms of the duration of fever, the advantage of baloxavir over oseltamivir was observed in the influenza type A (p < 0.001) and B (p < 0.001) subgroups and in the influenza A subtype H1N1pdm09 (p < 0.001) subgroup but not in the H3N2A subgroup (p = 0.430). The incidence of any AE was similar between the two groups (p = 0.260). The quality of the enrolled studies was high, and there was no publication bias.ConclusionIn pediatric patients with influenza, baloxavir results in a shorter duration of symptoms and fever compared to oseltamivir, which may be attributed to their different bioavailability and half-lives. Additionally, the safety profiles of baloxavir and oseltamivir are comparable.Systematic review registrationhttps://www.crd.york.ac.uk/, CRD420251128843.